Meningkatkan Keterampilan Berbicara Melalui Petualangan Gamastar Dalam Bahasa Indonesia - Kristia Setyaningsih; Ngatmini Ngatmini (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The purpose of this study is to improve the speaking skills and speaking skills of grade III students of SDN Pasekan 01 through the media Gamastar (Picture of Surrounding Problems). This form of research is class action research (PTK). Research is carried out in two cycles, each cycle has four stages, namely action planning, action implementation, observation and reflection. The subjects of this study were grade III students of SDN Pasekan 01 totaling 13 students. Data collection techniques are documentation, observation, tests and interviews. The data validation technique used is data validation. Data analysis techniques use comparative descriptive techniques. The conclusion of this research is that the application of Gamastar media can improve the speaking skills of grade III students of SDN Pasekan 01.